OFFICE WORK: ERGONOMIC AND MEDICAL ASPECTS - Berenyi, Laszlo; Szolnoki, Bernadett; Banhegyesi, Lajos (European Scientific Journal, ESJ, 2015)
A special attention must be given to office work in order to increase efficiency of the corporation and to preserve the health of the workforce. Physical work is easier to plan and to measure because the tasks are predictable and repeatable in a high volume. Office work includes various activities with difficulties in estimating time- and resource need. Physical and mental flexibility of people bridges the challenges of continuous working but there are many long term adverse effects. The paper looks the impacts of office work environment on the muscular-skeletal system of ergonomic perspective. People spend several hours every day sitting in front of the computer during work and non-work activities. Although technologically the development of computer technology is dynamic, people may criticize the results from the ergonomic point of view. Economic aspects and lack of knowledge together may lead to the development of a work environment, which discourages effective work. The most common problems come from the bad sitting posture, the wrong positioning of the mouse or the keyboard on the table and the improper selection of tools and gadgets in the direct work environment. These lead to mutation of human muscular-skeletal system. Next to this the static muscle load results short term problems as well. The experiences of our empiric research shows that factors of individual satisfaction may differ from the professional viewpoint of ergonomics and medical sciences. This is why exploring the possibilities of convergence is important, including knowledge dissemination or promotion of prevention exercises.